Biologically Based Merge of Wh-questions in the Bamboo Slips of Tao Te Ching - daoshan ma (PAROLE: Journal of Linguistics and Education, 2019)
The bamboo slips of Tao Te Ching is the earliest found version of the ancient Chinese classic philosophical work written by Li Er in the Spring Warring State Era. The merger operation of the wh-questions in the bamboo slips of Tao Te Ching is dealt with in this thesis. External merge of the wh-words is contrasted with the internal merge of wh-words in wh-questions and non-wh-words in topic structures of wh-questions in the bamboo slips of Tao Te Ching. The biologically localized merger is further discussed and proven by the experiment on the aphasic patients of the biscuits stolen story.